After #Charlottesville: Interrogating our Racist Past in the Trump Era - Boyce, Travis (Radical Teacher, 2018)
In wake of the violent and deadly events in Charlottesville and President Donald Trump’s response in which he effectively defended the Neo-Nazis and Confederate monuments, it’s important that college students understand the Lost Cause movement, the building of Confederate monuments and how college campuses are affected. In preparation for the fall 2017 semester, I revised my AFS 310 African Americans and U.S. Education syllabus in which I devoted the first five weeks of the semester to interrogating the aftermath of Charlottesville and this nation’s Confederate legacies on college campuses. Centering the unit’s theme on “The Lost Cause and the Collegiate Idea,” this article will discuss in depth the unit I taught as well as student assessment and outcomes upon completion of the unit.